A rapid self-healing glassy polymer/metal–organic-framework hybrid membrane at room temperature. Issue 10 (15th February 2023) - Niu, Qingyu; Han, Hang; Liu, Xiao; Li, Bin; Li, Huanrong; Li, Zhiqiang
Abstract : Owing to the multiconnected cross-linking effect of lanthanide MOFs and a high density of hydrogen bonds, a MOF-polymer hybrid membrane not only shows mechanical robustness, but also an instantaneous self-healing ability even in glassy state. Abstract : The development of repairable MOF-polymer hybrid materials will greatly extend their service life by repairing fractured parts on the spot; however, it is difficult for robust glassy polymers to self-heal below the glass transition temperature ( T g ) as the polymer network is frozen. We herein report glassy polyMOF-RHP hybrid membranes by integrating lanthanide polyMOF (polyLnMOF) with randomly hyperbranched polymers (RHP) bearing a high density of hydrogen bonds. Since crystalline lanthanide MOFs act as multiconnected cross-linking agents and cross-link the interpenetrating polymer network, the obtained polyLnMOF-polymer membrane shows enhanced mechanical strength with a storage modulus of 3.09 GPa and a T g up to 49 °C. Meanwhile, the high intersegment migration ability of the polyLnMOF-polymer network facilitates the exchange of hydrogen-bonded pairs even in the glassy state, leading to an instantaneous room-temperature self-healing ability. The polyLnMOF-polymer membranes inherit the ratiometric temperature-sensing behavior of pristine lanthanide MOFs, resulting in more processable temperature-sensing membranes. This work provides an appealing strategy for the design of mechanically robust, yet self-healing, MOF-polymer functional materials.